Attitudinal loyalty, brand value and brand loyalty in the agriculture produce retail industry / Abaidullah Mustaffa - Mustaffa, Abaidullah (Institute of Graduate Studies, UiTM, 2018)
This research analyzed brand loyalty of customers towards hypermarkets or retail stores of agriculture produce. Brand loyalty was studied using attitudinal loyalty and brand value to address the issue of fierce competition among retail stores of agriculture produce. Retaining loyal customers, attracting new customers and moulding them into brand loyal customers could generate accumulative sales growth and volume over time. Attitudinal loyalty comprises of three dimensions: cognitive loyalty, affective loyalty and conative loyalty. Brand value comprises of four component: value, quality, satisfaction and image. Quantitative approach using self-administered questionnaires with 5-point Likert scale was distributed to 420 respondents who were the customers of agriculture produce retailers…